Agile IT Governance for Digital Transformation at Manado State University: Implementation Strategy on Application Factors - Batmetan, Johan Reimon; Lumapow, Harol R.; Rawis, Joulanda A M; Palilingan, Verry Ronny (JR Education, 2025)
Digital transformation in the higher education environment demands adaptive and responsive information technology governance (IT Governance). Agile IT Governance is a relevant approach to improving university information technology systems' flexibility, effectiveness, and sustainability. This study explores the implementation strategy of Agile IT Governance on application factors at Manado State University. Using a qualitative approach with the SWOT analysis method and priority analysis using McFarlanGrid, this study identifies key factors that influence the adoption of Agile IT Governance, including organizational, technological, and policy aspects. The results of the study indicate that the success of implementing Agile IT Governance in universities depends on collaboration between stakeholders, digital infrastructure readiness, and an iterative approach to developing and managing applications. The implications of this study provide insight for higher education institutions in designing a more adaptive and sustainable digital transformation strategy at Manado State University.